Optoelectronics: Locally Welded Silver Nano‐Network Transparent Electrodes with High Operational Stability by a Simple Alcohol‐Based Chemical Approach (Adv. Funct. Mater. 27/2015). (14th July 2015) - Lu, Haifei; Zhang, Di; Cheng, Jiaqi; Liu, Jian; Mao, Jian; Choy, Wallace C. H.
Abstract : Welding the nanowire junctions is an effective strategy for reducing sheet resistance and improving operational stability of flexible nanowire electrode in practical applications. On page 4211, W. C. H. Choy and team develop a simple alcohol‐based chemical post‐treatment on silver nanowires for forming locally welded silver nano‐network electrode, without any assistance of heat, light, electrical current, nor mechanical pressure.